BIOTECHNOLOGICAL APPROACH TOWARDS BREAST CANCER - NASTARAN SADAT KHORRAMINIA; VIDYA TALE (International Journal of Pharma and Bio Sciences, 2016)
Breast cancer is an ancient disease which was discovered 3500 years ago in Egypt. Breast cancer is the common malignant tumor and second cause of death in women all over the world. It is heterogeneity, including intra tumor (genomic, transcriptomic) and inter tumor (angiogenesis, metastatic) heterogeneity, Therefore no single treatment is sufficient to cure all patients. The Development of Molecular Profiling using DNA Microarrays, proved this heterogeneity. To determine the best therapies for Breast cancer patients, many factors have involved classifying the Breast cancer such as: age, Lymph node status, hormone receptor and etc. Based on current research techniques like Gene expression profiling, Immunohistology, Breast cancer identified into four types: Estrogen and Progesterone Receptor Positive, Luminal A and Luminal B, HER2 and Basal Like, Triple Negative. Each type has different prognosis and treatment response. Most therapies for Breast Cancer are: Surgery, Radiation, and Chemotherapy. Current research in cancer includes the development of carriers to allow alternative dosing routes, new therapeutic Methods such as Hormonal Therapy and Targeted Therapy and Proteomics.